Kajian Siklus Urbanisasi Pada Wilayah Pinggiran Kota Semarang (Studi Kasus: Kecamatan Mijen) - Nuzullia, Laella; Setyono, Jawoto Sih (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
Mijen District as a peripheral area of Semarang has been urbanizing based on population growth and land development in the period 1993 – 2015. One of urbanization problems in Mijen district as peripheral area is land use change and increasing population, which caused by BSB new town development. Identification of urbanization stages in the peripheral area is expected as consideration for government to manage regional development effectively and efficiently. This research uses an urbanization cycle approach by Van Den Berg as a conceptual theory to identify the urbanization stages. In addition, the land development and its linkage with the population growth are also used to identify emerging problems, so that the government reduces its impact. The research shows Mijen District runs into the stage of urbanization, suburbanization, desurbanization/ counterurbanization and the absolute phase of decentralization in the period 1993 – 2015. Most of sub-districts in Mijen have sprawl characteristics which the land development of each sub-district is greater than population growth, so it indicates that the land usage is less. Otherwise,  Polaman, Jatisari, Mijen and Wonolopo have densification characters which each population growth is greater than the land development and  indicates that the lands are used effectively and efficiently.